Pembelajaran Pendidikan Agama Islam Anak Berkebutuhan Khusus dalam Konsentrasi Belajar di SLB Smart School Pacet - Nia Aulia; Juli Amaliyah Nasucha (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Islamic Religious Education (PAI) learning for children with special needs is a fundamental aspect in the formation of character, faith, and noble morals of students. This study deeply examines the learning of Islamic Religious Education (PAI) for children with special needs in the context of learning concentration at SLB Smart School Pacet, Mojokerto Regency, East Java. The study focuses on three main aspects: (1) how is the learning concentration of children with special needs in PAI learning at SLB Smart School Pacet; (2) how is PAI learning for children with special needs at SLB Smart School Pacet; and (3) what are the supporting factors of PAI learning for children with special needs in learning concentration at SLB Smart School Pacet. This research uses a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation involving the principal, PAI teacher, classroom teachers, parents, and students. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing/verification. Data validity was tested through source and technique triangulation. The results show that: (1) the learning concentration of children with special needs at SLB Smart School Pacet generally ranges from 0–10 minutes, but children with hearing impairment (tunarungu) and intellectual disability (tunagrahita) have a longer concentration span of 10–15 minutes; (2) PAI learning applies an expository strategy combined with various learning media including educational videos, visual aids (posters), and direct real-life/environmental media; and (3) supporting factors include internal factors (learning interest and learning motivation from within the students) and external factors (harmonious relationships between teachers and students, and between teachers and parents). This research contributes to the development of inclusive, humanistic, and adaptive PAI learning strategies and media for children with special needs in special education institutions..